A longitudinal analysis of the relationship between self-compassion and the psychological effects of perceived stress. Issue 6 (2nd November 2018) - Stutts, Lauren A.; Leary, Mark R.; Zeveney, Andrew S.; Hufnagle, Ashley S.
ABSTRACT: Self-compassion is consistently associated with psychological well-being, but most research has examined their relationship at only a single point in time. This study employed a longitudinal design to investigate the relationship between baseline self-compassion, perceived stress, and psychological outcomes in college students ( n = 462) when the outcomes were measured both concurrently with perceived stress and after a lag of six months. Self-compassion moderated the effects of perceived stress such that stress was less strongly related to depression, anxiety, and negative affect among participants who scored high rather than low in self-compassion. Self-compassion also moderated the effects of perceived stress on depression and anxiety prospectively after six months. Self-compassion predicted positive affect but moderated the effects of perceived stress on positive affect in only one analysis. This study suggests that high self-compassion provides emotional benefits over time, partly by weakening the link between stress and negative outcomes.